Unraveling access barriers and challenges of sexual and reproductive health services for individuals with psychosocial disabilities in Nigeria: insights from family, caregivers, and community stakeholders - Usman, Ibrahim Muhammad; Ruiter, Robert A. C.; Dilana, Schaafsma (Frontiers in Psychology, 2025)
BackgroundPsychosocial disability (PSD) refers to the limitations experienced by persons with mental illness (PWMI) in interacting with their social environment. Persons with psychosocial disabilities (PPSD) face significant barriers to accessing sexual and reproductive health (SRH) services due to structural and institutional barriers. Despite commitments under the Convention on the Rights of Persons with Disabilities (CRPD), there are persistent rights violations and denial of PPSD to exercise their rights and access services related to SRH care. This study aimed to explore the multifaceted barriers and enablers influencing access to SRH for PPSD in Nigeria, drawing from the perspectives of caregivers, family members, and stakeholders in the communities where they live.MethodsA qualitative study method was employed, using focus group discussions (FGDs). Sixty (N = 60) participants were purposively and conveniently selected to include caregivers, and family members of PPSD, and community actors’ who are familiar with mental health issues and its related PSD. Responses were coded and analyzed thematically, guided by the socio-ecological framework.ResultsThe study reported key barriers to SRH access for PPSD, including limited mental health awareness, stigma, financial constraints, and poor healthcare infrastructure. Enablers included community awareness, financial support from informal networks, mobile outreach and staff training. Notably, the study revealed a unique culturally specific belief, such as mental illness being transmitted through breastfeeding or bringing fortune through sexual contact with affected women.ConclusionThe study highlights critical and intersecting barriers to SRH access for PPSD in Nigeria, underscoring the need for inclusive, rights-based and support system friendly interventions addressing both community-level barriers and systemic health service gaps. The study found that caregivers’ engagement and leverage of local structures within the community are essential for improving the interaction of PPSD with their physical environment and enhancing access to SRH services. Further study and SRH policy efforts must prioritize socio-cultural approaches that uphold the dignity and rights of PPSD in the community.